Experimental Investigation on the Effect of Angles of Attack to the Flutter Speed of a Flat Plate in Axial Flow - I Putu Gede Sopan Rahtika; I Made Suarta; I Komang Rusmariadi; Putu Wijaya Sunu (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
The application of flat plates to the field of wind harvesting requires a lot of research toward the understanding of the flutter behavior of the plates. There are shortages of articles that discuss the effect of varying the angles of attack to the flutter speed of a flat plate. This research aims to conduct a basic experimental research on the effect of relative position of a thin-flat plates to the direction of the air flow to its flutter speed. In this study, a thin-flat plate was placed in a subsonic wind tunnel to test its flutter speed. The position of the plate was varied in various angles of attack. The effect of the angles of attack to the flutter speed was observed.